The reproducibility of dendritic cell and T cell counts to a 30-min high-intensity cycling protocol as a tool to highlight overtraining - Baker, C.; Piasecki, J.; Hunt, J. A.; Hough, J. (Experimental Physiology, 2024)
Heavy training has been reported to be immunosuppressive in athletes and lead to blunted cortisol responses to exercise. Cortisol elevates the number of dendritic cells (DCs), key antigen-presenting cells that interact with T cells to initiate an immune response. Reproducible cortisol responses to a 30-min cycle test have been identified but were based on percentage of work rate maximum. To ensure physiological consistency, submaximal anchors, that is, ventilatory threshold (VT1) should prescribe intensity. This study aims to assess the reproducibility of the DC and T cell responses to an adapted stress test to assess its usefulness in assessing DC dysfunction with intensified training. Twelve males cycled for 1 min at 20% below VT1 and 4 min at 50% between VT1 and VO2max, for 30 min (20/50), with blood samples pre-, post- and 30 min post-exercise. This was repeated twice, 2-7 days apart. Flow cytometry assessed total DCs, plasmacytoid DCs, myeloid DCs, total T cells, T helper cells and T cytotoxic cells. No significant trial or interaction effects were found for any variable. A significant main effect of time for all variables was found; immune cells increased from pre- to post-exercise and decreased to baseline 30 min post-exercise, apart from plasmacytoid DCs, which remained elevated 30 min post-exercise. Intraclass correlation coefficients showed overall good-to-excellent reliability for all immune cells, with smallest real difference and Bland-Altman analysis verifying high reproducibility between trials. These results suggest that the 20/50 exercise test induces reproducible DC and T cell count changes, which, implemented before and after a period of intensified training, may highlight the negative states of overtraining.